The meaning of compulsive exercise in women with anorexia nervosa: An interpretative phenomenological analysis. (March 2016) - Kolnes, Liv-Jorunn; Rodriguez-Morales, Lymarie
Abstract: Background: Despite the substantial role of compulsive exercise in the development and maintenance of anorexia nervosa, and despite associated risks of medical complications, longer length of hospitalization and higher relapse rates, little is understood about the personal experience and meaning of compulsive exercise in this context. This study explored the experiences of compulsive exercise in women with anorexia nervosa, restrictive type, and the sense they make of these experiences in the context of their daily lives and treatment programme. Methodology: Semi-structured interviews were conducted with six females, four of whom were former athletes. Transcripts were subjected to interpretative phenomenological analysis (IPA). Findings: This paper reports on the first superordinate theme, paradoxical functions of exercise. An account of the participants' perspectives regarding their engagement with compulsive exercise as a means of emotion regulation is presented first. Secondly, the manner in which participants experience the embodiment of emotional states is explored. Thirdly, the ability of exercise to offer participants a sense of time-out is presented. Finally, the meaning of exercise in relation to the participants' sense of self and identity are analysed. Conclusions: The study demonstrates how compulsive exercise represents an essential means of emotion distraction and management for individuals with anorexia nervosa. The finding that feelings are echoed in the participants' bodies is significant, as this gives participants a sense of connecting with their emotions. The time outs offered by exercise provide a degree of structure, control and stability for the participants' sense of self, helping them commit to the demands of treatment. However, this control and stability is short lived, as it may lead to a subsequent loss of control if underlying concerns and emotions are not addressed. It is suggested that interventions should aim to increase recognition and tolerance of negative feelings. Body-oriented and physical therapy interventions tailored specifically to individuals with anorexia nervosa may provide a fresh way of addressing emotions that is complementary to other therapies. Highlights: Compulsive exercise can be an essential part in emotion distraction and management for individuals with anorexia nervosa. How feelings are echoed in the participants' bodies and how awareness of embodied problematic feelings may enable understanding and regulation of emotions. Exercise embodies genuine significance for identity and belonging. By enhancing contact with the body and bodily sensations through body oriented approaches, patients may attune themselves to their emotions more easily.